Multifunctional magnonic platform based on the interplay between spin-wave waveguide and nanodots with PMA and DMI - Szulc, Krzysztof; Zelent, Mateusz; Krawczyk, Maciej (AIP, 2025)
Materials with perpendicular magnetic anisotropy (PMA) and antisymmetric exchange interactions are widely explored in spintronics but are of limited use in magnonics due to high damping. We present a hybrid magnonic crystal composed of a chain of circular nanodots with strong PMA and Dzyaloshinskii–Moriya interaction (DMI), positioned above a spin-wave waveguide made of permalloy. Due to the dipolar coupling between the subsystems, a strongly bound hybrid magnetization texture is formed, with two stable magnetization states in the nanodots: a single-domain state and an egg-shaped skyrmion state, allowing reprogramming of the system properties. Numerical results show complex spin-wave spectra with several key features for magnonics: programmable Bragg and non-Bragg bandgaps correlated with magnon–magnon couplings, the flat bands and bound states for the skyrmion state, and exclusively waveguide-dominated modes for the single-domain state. With these properties, the proposed hybrid magnonic crystal has different functionalities that overcome the damping limitations of materials with PMA and DMI and open up potential applications in spin-wave filtering, spin-wave generation, quantum magnonics, and analog magnonics, in particular in the realization of magnonic neural networks.
Keywords: magnonics; skyrmion; magnonic crystal; spin wave; DMI